1982
DOI: 10.1159/000265174
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Radioactivity in the Eyes of Rats after Injection of Iodinated Prolactin

Abstract: The present study involves the intracardial injection of iodinated ovine prolactin into albino rats and the autoradiographic demonstration of patterns of isotopic incorporation into ocular tissues, including the retina, choroid coat and ciliary body. Control procedures include the utilization of competitive hormonal binding, a comparison of the radioactive pattern in eyes after the injection of iodinated beef serum albumen and an autoradiographic evaluation of the thyroid glands of all groups. The competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…PRL is found in the aqueous humor of the human eye (29,68), and both PRL and vasoinhibins are present in rat retina (3,71). Some ocular PRL may originate from systemic PRL entering the eye because iodinated PRL injected intracardially can be incorporated into the retina, choroids, and ciliary body (62). However, PRL and vasoinhibins can also be synthesized intraocularly.…”
Section: Vasoinhibins Are Natural Inhibitors Of Ocular Angiogenesismentioning
confidence: 99%
“…PRL is found in the aqueous humor of the human eye (29,68), and both PRL and vasoinhibins are present in rat retina (3,71). Some ocular PRL may originate from systemic PRL entering the eye because iodinated PRL injected intracardially can be incorporated into the retina, choroids, and ciliary body (62). However, PRL and vasoinhibins can also be synthesized intraocularly.…”
Section: Vasoinhibins Are Natural Inhibitors Of Ocular Angiogenesismentioning
confidence: 99%
“…PRL is expressed throughout retina [4]. One animal study proved that intracardiac radioactive PRL injection will incorporate into ocular tissue [8]. A study reported that PRL level is increased in diabetics and it is lower in patients with retinopathy than in diabetics without retinopathy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Vasoinhibins are present in the retina (6), and because radioactive PRL injected intracardially is incorporated into ocular tissues (ciliary body, choroid, and retina) (7), we reasoned that a portion of ocular vasoinhibins could originate from the intraocular cleavage of PRL coming from the circulation; therefore, high levels of serum PRL in diabetic patients may restrain DR progression.…”
mentioning
confidence: 99%